2000
DOI: 10.1093/brain/123.6.1092
|View full text |Cite
|
Sign up to set email alerts
|

Differential adhesion molecule requirements for immune surveillance and inflammatory recruitment

Abstract: Activated CD4 Th1 lymphocytes can enter the brain in the absence of an inflammatory focus. However, the molecular mediators that regulate this early migration of lymphocytes into the brain have remained unclear. We hypothesized that the entry of these 'pioneer' lymphocytes into the brain is regulated by a set of molecular events that are distinct from those used once inflammation has been established. Using cells fluorescently labelled with the lipophilic dye DiI, myelin basic protein (MBP)-specific CD4 lympho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
138
3

Year Published

2003
2003
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 206 publications
(146 citation statements)
references
References 30 publications
5
138
3
Order By: Relevance
“…P-selectin binding through ligands presented on PSGL-1 is required for circulating murine T cells to enter the intrathecal compartment, in a migration pattern that is proposed to support immune surveillance of the CNS (17). We found that all CD4 ϩ ͞CD45RO ϩ T cells in CSF from patients with NIND, as in PB, expressed PSGL-1 (Fig.…”
Section: Resultsmentioning
confidence: 74%
See 2 more Smart Citations
“…P-selectin binding through ligands presented on PSGL-1 is required for circulating murine T cells to enter the intrathecal compartment, in a migration pattern that is proposed to support immune surveillance of the CNS (17). We found that all CD4 ϩ ͞CD45RO ϩ T cells in CSF from patients with NIND, as in PB, expressed PSGL-1 (Fig.…”
Section: Resultsmentioning
confidence: 74%
“…Pioneer lymphocytes, proposed to perform immune surveillance, were detected in murine choroid plexus and leptomeninges (5,17). To assess whether human T cells might traffic similarly, we analyzed sections of choroid plexus from seven individuals.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, the differences between meningeal and parenchymal CNS blood vessel endothelial cells extend to differences in their expression patterns for P-and E-selectin. In the healthy CNS, meningeal blood vessel endothelial cells can be distinguished from those in the CNS parenchyma by their constitutive expression of P-selectin, which is absent from endothelial cells of parenchymal blood vessels (17,28). Furthermore, injection of proinflammatory cytokines into mice induced expression of E-selectin in meningeal but not in parenchymal CNS blood vessel endothelial cells (25).…”
Section: Discussionmentioning
confidence: 99%
“…The migration of autoreactive T cells to sites of the autoimmune attack is critically dependent on the interaction of adhesion molecules on these cells with their ligands such as VCAM-1, ICAM-1, CD31, and LFA-1 on tissues in the target organ (31)(32)(33)(34)(35). Thus, the delayed onset and reduced severity of EAE in anti-MIF-treated mice appeared to be the consequence of the decreased expression of VCAM-1 in the CNS.…”
Section: Discussionmentioning
confidence: 99%